Magnetization roasting combined with multi-stage extraction for selective recovery of lithium from spent lithium-ion batteries - Yuan, Xue (2024)
Lithium-ion batteries recycling is crucial for environmental protection and resource conservation. Among the battery components, lithium holds high value, but current recovery methods exhibit limited efficiency in selectively extracting lithium from spent electrode materials. In this study, we propose a novel pathway that combines magnetization roasting with multi-stage extraction to enhance the recovery of lithium from spent electrode materials. The process begins with the decomposition of the spent ternary cathode material into CoO, NiO, MnO, Co, and Ni at 600 ℃ for 30 min using pyrolysis product-derived reducing agents. Heat-induced magnetization of the cathode plates facilitates magnetic separation, effectively isolating cathode, and anode plates. The cathode material can be recycled by water impact crushing combined with sieving, and 40.80 % lithium dissolves into water for recycling. The comprehensive recycling efficiency of lithium is up to 95.30 % after carbothermal reduction with 15 % carbon addition. The sub-microlevel migration behavior of lithium ions in the proposed scheme was also examined for further mechanistic insights.